BINĀ’ AL NAZHARIYAH AL LUGHAWIYYAH FÎ AL TURAST AL ‘ARABIY WA TAQWÎMUHĀ - Roviin Roviin (STIQ Amuntai, 2020)
Indeed humans live in a specific environment and receive the language of this environment by acquiring it with a certainty of its vocal, grammatical, and semantic, as well as with knowledge of social rules in understanding and producing speech. Although linguists agree on this fact in language acquisition, they differ in their views on the acquisition process. Every opinion is based on a theory towards the nature of language. This research aims to explain and evaluate the linguistic theory in Arabic heritage. The researcher reads deeply the references, After a comprehensive understanding is formed on the object of the research, the researcher analyzes and realizes this information. The results of this research indicate that the Arabic heritage took place in the various theories presented by Arab linguists, namely “analysis” and “classification”. The various assumptions and theories used by the Arab linguistic heritage to classify the language and to describe it can be combined in an interference group of circles representing the general structure of the linguistic classification theory, as the various assumptions define and visualize their location from each other. So, the Arabic lesson needs to be reviewed and described as taxonomic rather than a standard lesson. Keywords: Linguistic theory, Arabic Heritage, Evaluation.